Passive fault-tolerant sliding mode attitude control for flexible spacecraft with faulty thrusters. (October 2014) - Mirshams, M; Khosrojerdi, M; Hasani, M
The attitude control subsystem plays a significant role in the overall performance of the spacecraft. Attitude control subsystem is vitally important to design the control system with rapid response performance, high control precision and insensitive to external perturbations. In this paper a novel fault-tolerant control design technique against faulty thrusters is investigated. This technique uses adaptive sliding mode control with application to spacecraft attitude maneuvering control system. The principle of the proposed fault-tolerant control scheme is to design sliding mode attitude controller using the time variable sliding surface to compensate the effect of partial loss of the actuators effectiveness. This adaptive law calculates the ability of spacecraft maneuvering in following the control input based on kinematic energy of the estimated and real model of the spacecraft. It is shown that the presented controller can accommodate the actuator faults, even while resisting the external disturbances. Moreover, in the control law scheme the effect of actuator saturation/constraint has been considered. An additional advantage of the proposed fault-tolerant control strategy is that the control design does not require a fault detection and isolation mechanism to detect, separate, and identify the actuator faults on-line. The associated stability proof is constructive and accomplished by the development of Lyapunov function candidate, which shows that the attitude orientation and angular velocity will globally asymptotically converge to zero. Moreover, several numerical examples are presented to demonstrate the efficacy of the proposed controller despite the external perturbations, moment of inertia uncertainty and faulty actuators. The numerical results clearly demonstrate the good performance of the adaptive sliding mode control despite the actuator fault comparison with some other controllers.